2014
DOI: 10.1177/0192513x14530972
|View full text |Cite
|
Sign up to set email alerts
|

A Demands and Resources Approach to Understanding Faculty Turnover Intentions Due to Work–Family Balance

Abstract: Using data collected on tenure-line faculty at a research-intensive Midwestern university, this study explored predictors of faculty job turnover intentions due to a desire for a better work-family balance. We adopted Voydanoff's theoretical framework and included demands and resources both within and spanning across the work and family domains. Results showed that work-related demands and resources were much stronger predictors of work-family turnover intentions than family-related demands or resources. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 76 publications
1
34
0
Order By: Relevance
“…*The academic work environment is characterized by poor working condition, job dissatisfaction (Kinman and Jones, 2008), workload (Almer et al, 2016), long working hours, high job demands (Watanabe and Falci, 2016) and occupational stress (Opstrup and Pihl-Thingvad, 2016). Such an environment often creates an imbalance between work and family lives and may result in undesirable outcomes such as stress (Opstrup and Pihl-Thingvad, 2016), and turnover intention (Barnes et al, 1998;Kinman and Jones, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…*The academic work environment is characterized by poor working condition, job dissatisfaction (Kinman and Jones, 2008), workload (Almer et al, 2016), long working hours, high job demands (Watanabe and Falci, 2016) and occupational stress (Opstrup and Pihl-Thingvad, 2016). Such an environment often creates an imbalance between work and family lives and may result in undesirable outcomes such as stress (Opstrup and Pihl-Thingvad, 2016), and turnover intention (Barnes et al, 1998;Kinman and Jones, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The BHERI Faculty Survey^conducted by the Higher Education Research Institute (USA) in 2010-2011 showed that only 32 % of faculty have a healthy balance between work and family life and poor balance leads to loss of job satisfaction and success. There remains much scope for improvement in Work-Family Balance (WFB) in the academic profession, throughout the world (Watanabe and Falci 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Academic staff turnover has an impact on the individual (Watanabe, & Falci, 2016), their colleagues (O'Meara, Lounder, & Campbell, 2014), and departmental budgets. Ketchen Jr. et al, (2017) recommend the strategic retention of staff through individual interventions and organisation-wide systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, O'Meara, Lounder, and Campbell (2014) suggest that academic staff may hide their true reasons for leaving an HEI, allowing administrators and managers to imagine either that the individual found themselves inadequate for the demands of their current post, or that they could not resist a superior post elsewhere. The literature suggests that it is often the failure of the academic workplace to meet individuals' expectations, and individuals' perception that their particular needs are not being acknowledged or met, that lie at the heart of academic staff turnover (see, Bucklin et al, 2014;Gourlay, 2011;O'Meara, Bennett, & Neihaus, 2016;O'Meara, Lounder, & Campbell, 2014;Robyn & Du Preez, 2013;Smith, 2010;Watanabe & Falci, 2016;Wilson, 2013;Yan, Yue, & Niu, 2015).…”
Section: Retentionmentioning
confidence: 99%